Ekspedisi Revitalisasi Permainan Matematika Geogram untuk Penguatan Konsep Geometri : Kegiatan di SMAN 2 Tarakan - R, Nurmala; Mucti, Alfian; Suciati; Hermansyah (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This Community Service Program aims to revitalize and implement Geogram (Geometry Tangram) as an innovative learning medium to address the difficulties faced by students at SMAN 2 Tarakan in visualizing and internalizing geometry concepts. The method employed was Participatory Action Research (PAR), involving teachers and 32 students. The main stages included Needs Assessment via Focus Group Discussions (FGD), the Revitalization of Geogram (which resulted in the Geogram media and a comprehensive guide book), and the Implementation Phase utilizing hands-on, Geogram-based expeditions. The activity results demonstrated a significant impact. Quantitatively, 92% of the students reported that learning geometry became easier and more enjoyable after using Geogram. Qualitatively, the program successfully fostered a supportive and innovative learning climate. The hands-on approach proved effective in overcoming conceptual difficulties, as students showed a much better understanding of the difference between rotation and reflection following the practical sessions. The success of the program was cemented by SMAN 2 Tarakan’s formal commitment to permanently integrate Geogram into its learning media bank. This signifies the achievement of the objective for Science and Technology transfer and positions the program as a model of best practice in enhancing spatial and geometrical literacy. Geogram proved itself to be an effective instrument for bridging the gap between abstract visual representation and robust conceptual understanding.